PENGARUH CITRA BPR, KUALITAS PELAYANAN, NILAI NASABAH, KEPERCAYAAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH TABUNGAN PADA BANK PERKREDITAN RAKYAT (BPR) LUGAS DANA MANDIRI CABANG SOLOK - Dettrita Dettrita (STKIP PGRI Sumatera Barat, 2021)
This research aims to analyze: 1) the influence of BPR pictures on honest loyalists. 2) The effect of service quality on loyal customers. 3) The impact of customer value in customer loyalty. 4) The influence of customer trust on customer loyalty. 5) The result of customer satisfaction on customer loyalty. 6) The impact of quality service on customer satisfaction. 7) The influence of customer value in customer satisfaction. Research results are: (1) BPR images have a positive and significant impact on customer loyalty; (2) Service quality has a positive and significant impact on customer loyalty; (3) Customer value has a positive and significant impact on customer loyalty Significant impact, (4) trust has a positive and important impact on customer loyalty, (5) customer satisfaction has a positive and important impact on customer loyalty, (6) service quality has a positive and important impact on customer satisfaction (7) Customer value has a positive and significant impact on customer satisfaction.